TREN DAN ARAH PENELITIAN PEMBELAJARAN BAHASA DI SEKOLAH DASAR PADA ERA DIGITAL: KAJIAN LITERATUR - Evika Widya Puspita; Putri Yanuarita Sutikno; Haryadi; Bernadus Wahyudi Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the trends, directions, theories, approaches, methods, and research gaps in language learning research at the elementary school level in the digital era. The study employed a literature review method by systematically examining national and international journal articles published between 2020 and 2025 that focus on language learning, educational technology, and digital innovation in primary education. The findings indicate that recent research trends emphasize the implementation of innovative, technology-integrated learning models such as Problem-Based Learning (PBL), Game-Based Learning (GBL), Blended Learning, and Project-Based Learning, which have been shown to enhance students’ literacy, motivation, and communication skills. Theoretical foundations commonly used include constructivism, connectivism, and social-cognitive learning theories, with dominant research approaches being Research and Development (R&D) and quasi-experimental designs. The review identifies several research gaps, including the limited integration of artificial intelligence, digital learning analytics, and long-term evaluations of technology-based language learning effectiveness in elementary education. This review provides a comprehensive overview of the future research directions, highlighting the importance of integrating innovative pedagogical approaches and digital technology to foster relevant and meaningful language learning in the 21st century.